Interests, Knowledge and Evaluation: Alternative Approaches to Curriculum Evaluation - Aoki, Ted T. (Alberta Journal of Educational Research, 2024)
Reprinted with permission from Aoki, T. (1986). Interests, knowledge and evaluation: Alternative approaches to curriculum evaluation. Journal of Curriculum Theorizing, 6(4), pp. 27–44. https://journal.jctonline.org/index.php/jct/issue/view/95